Comparative Experimental Evaluation of a Three-Phase ARCP Inverter With a Single Shared Inductor Using SiC MOSFETs and Si IGBTs - Lehmeier, Thomas; Amler, Adrian; Zhou, Yan; März, Martin (IEEE Applied Power Electronics Conference & Exposition (APEC 2024), 2024)
Using soft-switching, the efficiency and EMI performance of power inverters for drive and grid applications can be improved. An advantageous topology is the well-known auxiliary resonant commutated pole (ARCP) inverter. The novel single shared inductor S2I-ARCP is a modification of the conventional ARCP which saves two resonant inductors in the auxiliary circuit in case of a three-phase inverter application. This paper compares the use of SiC MOSFETs with Si IGBTs as main switches and the possible gain in efficiency compared to hard-switched implementation. The S 2 I-ARCP topology is implemented with a suitable control algorithm and tested at up to 15 kW with an 800 V dc-link. It is shown that at a switching frequency of 30 kHz, soft-switching can reduce losses by approximately 50% for configurations using either SiC MOSFETs or Si IGBTs as main switches. For both cases, the efficiency peaks at 99.65% and 98%, respectively.<br

Evaluation of Current, Delay, and Temperature Influence and Diode Selection on the Switching Behavior of a SiC/Si Hybrid Switch - Amler, Adrian; März, Martin (IEEE Applied Power Electronics Conference & Exposition (APEC 2024), 2024)

Forward Recovery and its Mitigation in Hybrid Si/SiC-based DC–AC Converters - Zhou, Yan; Lehmeier, Thomas; Amler, Adrian; März, Martin (2025 IEEE Applied Power Electronics Conference and Exposition (APEC), 2025)
The ongoing progress in the field of wide bandgap (WBG) devices enables new topologies and unmatched power density in high-power dc–ac converters. However, the still high cost of WBG devices, such as silicon carbide (SiC) MOSFETs, continues to hinder their widespread adoption in commercial converters. To address this challenge, emerging hybrid topologies combine fast-switching SiC MOSFETs with Si IGBTs operating at the fundamental frequency, achieving an optimal balance between cost and performance. In such topologies, the rapid switching of SiC devices induces high current slew-rates, which trigger forward recovery effects in the IGBTs. This phenomenon leads to additional losses in these bipolar devices and generates transient overvoltages, compromising the converter’s reliability. This article investigates the forward recovery behavior of different IGBT technologies and explores the mitigation by introducing a snubber capacitor to decouple the different stages of the topology. The results demonstrate the effectiveness of this approach in mitigating the detrimental impacts of forward recovery in hybrid dc–ac converter
Keywords: Insulated gate bipolar transistors; MOSFET; Silicon carbide; Snubbers; Capacitors; Switches; Silicon; Topology; Transient analysis; Surges

IGBT Comparison for Optimized Switching Behavior in the SiC/Si-Hybrid Switch - Amler, Adrian; Heckel, Thomas; Ruppert, Daniel; Retter, Cornelius; März, Martin (2025 IEEE Applied Power Electronics Conference and Exposition (APEC), 2025)
The parallel connection of Si-IGBTs and SiC-MOSFETs in a so-called hybrid switch offers new degrees of freedom to optimize the efficiency of bridge-type inverters and converters. By separately controlling the parallel devices with a gate delay, the switching performance can be improved to resemble that of the superior MOSFET. It is known that the optimal switching strategy depends on the operating point (temperature, current) and the hybrid switch design (chip area ratio, gate resistance). Additionally, the switching and conduction behavior changes drastically when using different IGBT technologies and devices. The comprehensive experimental study performed for this paper demonstrates that the IGBT technology used has a strong influence on the system efficiency as a result of its forward characteristics and its turn-OFF performance and gives an overview of the relevant dependencies. Different established and state-of-the-art IGBTs are tested in a double pulse setup and compared regarding their switching performance in the hybrid switch. It is shown that the hybrid switch variants can achieve from up to 54 % to 71 % system loss reduction compared to a standalone IGBT system depending on the device selection. It thus performs on-par with SiC MOSFETs under comparable operating condition

Improved Capacitive Power Transfer with Non-Resonant Power Transfer Link using Radio Frequency Push-Pull Inverter - Amler, Adrian; Weitz, Nikolai; März, Martin (IEEE Journal of Emerging and Selected Topics in Power Electronics, 2022)
In recent years, research on Wireless Power Transfer and Switched-Mode Power Supplies with a capacitive coupling link has been on the rise. Whereas many researchers investigate resonant coupling links, often resulting in tough requirements for the involved inductors, this paper focuses on the elimination of all inductive components in the coupling link and the rectifier through the use of a non-resonant capacitive link. We propose a converter with a resonant single-ended push-pull inverter operating at radio frequencies of e.g. 13.56 MHz to directly drive the non-resonant capacitive power transfer link. The ability of the converter to operate at a high frequency and to facilitate a significant voltage change across the link capacitors improves the power transfer characteristics of the system compared to previously published systems with a non-resonant capacitive link. Said combination is also beneficial for the transient behavior, parameter variation robustness, an easy design process, simplified drive requirements, and a predictable and limited capacitor voltage stress. The presented converter transmits 122.9 W across an effective link capacitance of 120 pF, leading to the highest input voltage-normalized power transfer to link capacitance value of 13.7 W/(nF∙V) among previously published capacitive power transfer systems with a non-resonant link.
CRIS-Team Scopus Importer:2022-09-09
Keywords: Behavioral sciences; Capacitance; Capacitive coupling; Capacitors; Couplings; high-frequency power converters; Inductors; Inverters; resonant inverters; Topology; wireless power transfer

On the Influence of the Parasitic Capacitance of a Bridge Rectifier on Series-Resonant Capacitive Wireless Power Transfer Systems - Amler, Adrian; Weitz, Nikolai; März, Martin (2022 IEEE Energy Conversion Congress and Exposition, ECCE 2022, 2022)
Capacitive wireless power transfer systems often rely on high frequency power converters and incorporate a resonant coupling link. The input capacitance of a bridge rectifier alters the overall power transfer of a capacitive power transfer system with a series-resonant transfer link. In this field, most analytic converter models are based on a representation of the rectifier as an equivalent resistance, thus neglecting the parasitic properties and the switching behavior of the rectifier. In this paper, studies on said issue are conducted by using a complex power and a time-domain approach. It is shown that through an extension of the capacitance at the rectifier input the transferred power can be increased. An optimal value for the rectifier input capacitance exists, thus maximizing the power. The rectifier capacitance creates an additional degree of freedom in the converter design, influences the soft switching behavior of the inverter, and may be used to improve robustness against a variation of the link capacitance.
Created from Fastlane, Scopus look-up
Keywords: Capacitive Power Transfer; HF Power Conversion; Wireless Power Transfer

Three-Phase ARCP Inverter Using Soft-Switching with a Single Shared Inductor - Lehmeier, Thomas; Amler, Adrian; Zhou, Yan; März, Martin (IEEE Transactions on Power Electronics, 2023)
Soft-switching in power inverters for drive and grid applications can both enhance the efficiency by reducing switching losses and improve EMI due to lower switching speeds with their associated dv/dt. An advantageous topology is the well-known auxiliary resonant commutated pole (ARCP) inverter. The development of such power electronic inverters often focuses on reducing weight, volume, and cost. Considering a three-phase ARCP system, this article presents a novel single shared inductor (S²I) -ARCP approach to reduce the passive component count in the auxiliary circuit from three to one. The simultaneous use of the shared inductor by more than one phase must be detected and avoided by the control algorithm. A frequency analysis of such occurrences is performed, and a method for avoiding them by shifting the switching edges is presented. The proposed S2I-ARCP topology together with an appropriate control algorithm is implemented and validated at 10 kW with an 800 V DC-link. Efficiency measurement results indicated a significant loss reduction under soft-switching operation by more than 38% compared to hard-switching, with a peak efficiency value of 99.58%. It is demonstrated that a mere adjustment in the control signal generation can save two resonant inductors without significant disadvantages.<br
Keywords: Auxiliary resonant commutated pole (ARCP); collision avoidance; electromagnetic interference (EMI); reduced passive component count; single shared inductor; soft-switching technique; three-phase inverter; two-level topology; zero-current switching (ZCS); zero-voltage switching (ZVS); Inductors; Inverters; Topology; Switching circuits; Switches; Electromagnetic interference; Snubbers